Air quality monitoring at an indoor location - Tonmoy, Tahsin Abrar; Chakraborty, Prashanta; Ahmed, Imtiaz Uddin; Jakaria, Hasan Mohammad (Brac University, 2024)
This final year design project is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Electrical and Electronic Engineering, 2023.